DIGITAL SIGNALING SYSTEM FOR IOT ECOSYSTEMS - Lastre Olazábal, Guillermo; García Cabrera, Gilbert Rafael (Telemática, 2023)
In this work, a Digital Signaling application is implemented that, at the hardware and software level, allows centralized, dynamic, and secure control of multiple screens in a single interface. It can be inserted into an IoT ecosystem through the MQTT protocol, which allows it to react to certain situations detected by sensors or other devices, dynamically changing the content displayed on the screens. In addition, IoT platforms are deployed that allow the management and monitoring of the screens, both within the local network (edge) and based on the cloud. Its operation is demonstrated with a case study where the screen changes the image shown when a motion sensor detects people and turns on the lights of the premises that remain off. At the same time, there were no people in it. This way, energy is used efficiently since it is only activated when necessary.